From Santa Anna to Selena : notable Mexicanos and Tejanos in Texas history since 1821 - Joseph, Harriett Denise (University of North Texas Press, 2018)
"A collection of portraits of important people either from Mexico or of Mexican heritage, who had an influence on Texas history. Time period begins in 1821 when Mexico achieved independence from Spain, up to the present."--Publisher